Dynamic reconfiguration of functional brain networks supporting response inhibition in a stop-signal task - Wang, Bin; Hao, Yaqing; Zhan, Qionghui; Zhao, Shuo; Li, Dandan; Imtiaz, Sumaira; Xiang, Jie; Wu, Jinglong; Fukuyama, Hidenao; Yan, Ting (Brain imaging and behavior, 2020)
Response inhibition is the ability to suppress automatic actions or behaviors that are not appropriate or are no longer adaptive to the situation. Although many studies have suggested regional brain activation, the nature of the reconfiguration of functional brain networks involved in response inhibition remains unknown. Here, we assessed brain changes associated with response inhibition using graph theoretical analysis applied to functional connectivity data acquired while subjects performed a simple stop-signal task. We identified several ways in which global network organization shifted to meet the demand for response inhibition. Increased demand for response inhibition was associated with a global network configuration with more efficient communication across the network (functional integration) and more specialized processing (functional segregation). Regions distributed in the frontoparietal network and attention networks were found to be highly efficient in the stop condition. Nodal efficiency was significantly associated with reaction time and showed a different pattern between the go and stop conditions. In addition, the conditional differences (stop vs. go) in nodal efficiency and regional task activation were common in the postcentral gyrus (PoCG) and superior temporal lobe gyrus (STG), and a negative correlation between these differences was found in the frontal and parietal lobes. These results provide compelling evidence that response inhibition is associated with truly global changes in brain functional connectivity and additional insights into how defects in response inhibition are associated with neurological or psychiatric difficulties.